Solid-state battery

By using resin, spherical carbon material and fibrous carbon material resin collector in solid batteries, combined with Si-based active substances, the capacity reduction problem caused by expansion or contraction of the active substance layer is solved, and the capacity maintenance rate is improved and Simplification of constraint pressure.

CN119275293APending Publication Date: 2025-01-07TOYOTA JIDOSHA KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410868644.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-04
Filing Date
2024-07-01
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The expansion or contraction of the active material layer during the charging and discharging of the conventional solid batteries resulted in the ion conduction path and the electron conduction path being cut off, resulting in a reduced capacity maintenance rate, and a large constraint fixture is required to apply a high constraint pressure to suppress this problem.

Method used

A resin current collector including resin, spherical carbon material and fibrous carbon material is used, and Si-based active substance is added to the active substance layer, and conductive paths are connected through spherical carbon material and fibrous carbon material to inhibit peeling of the active substance layer and Reduced capacity.

Benefits of technology

It effectively suppresses the reduction of discharge capacity, improves capacity maintenance, simplifies the demand for constraint pressure, and reduces the dependence on large constraint fixtures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275293A_ABST
    Figure CN119275293A_ABST
Patent Text Reader

Abstract

The invention relates to a solid-state battery. Provided is a solid-state battery in which a decrease in discharge capacity is suppressed. This solid-state battery is provided with an electrode that has: a resin current collector that contains a resin, a spherical carbon material, and a fibrous carbon material; and an active material layer containing an active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to solid state batteries. Background Art

[0002] In recent years, secondary batteries such as lithium-ion secondary batteries have been suitably used as portable power sources for personal computers, portable terminals, etc., and as power sources for driving vehicles such as electric vehicles (BEV), hybrid vehicles (HEV), and plug-in hybrid vehicles (PHEV).

[0003] In secondary batteries, since an electrolyte containing a flammable organic solvent is used, a safety device to suppress the temperature rise during a short circuit is required, and improvements in the structure or materials for preventing short circuits are required. In contrast, for solid batteries that convert the electrolyte into a solid electrolyte layer and solidify the material, since no flammable organic solvent is used in the battery, the safety device can be simplified, and it is believed that the manufacturing cost and productivity are excellent.

[0004] The current collector of a conventional solid battery has a single-layer structure composed of a ceramic foil or a metal foil, or a laminate including a ceramic foil and a metal foil (for example, Japanese Patent Application Publication No. 2017-112029). Summary of the invention

[0005] Problems to be solved by the invention

[0006] However, in the conventional solid battery including a collector including ceramic foil and / or metal foil, when the active material layer expands or contracts due to the rapid increase or release of the active material during the charge and discharge process, the ion conduction path and the electron conduction path are easily cut off, and the capacity retention rate is easily reduced. In Japanese Patent Publication No. 2017-112029, in order to suppress the peeling of the active material layer, the solid battery is fixed with a constraint fixture and a constraint pressure is applied, but in order to apply a high constraint pressure, a large constraint fixture is required, and there is still room for improvement.

[0007] Therefore, in view of the above-mentioned actual situation, an object of the present disclosure is to provide a solid battery in which a decrease in discharge capacity is suppressed.

[0008] Means for solving problems

[0009] Means for solving the above-mentioned problems include the following means.

[0010] <1> A solid battery comprising an electrode including: a resin current collector containing a resin, a spherical carbon material, and a fibrous carbon material; and an active material layer containing an active material.

[0011] <2> The solid battery according to <1> above, wherein the active material includes a Si-based active material.

[0012] <3> The solid battery according to <1> or <2>, wherein the resin has a softening temperature of 30° C. or higher and 80° C. or lower.

[0013] <4> The solid battery according to any one of <1> to <3> above, wherein the spherical carbon material comprises acetylene black (AB), and the content of the spherical carbon material is 2% by mass or more and 13% by mass or less relative to the total solid content of the resin collector.

[0014] <5> A solid battery according to any one of <1> to <4> above, wherein the fibrous carbon material comprises vapor grown carbon fiber (VGCF), and the content of the fibrous carbon material is greater than 15 mass % and less than 25 mass % relative to the total solid content of the resin collector.

[0015] Effects of the Invention

[0016] According to the present disclosure, a solid battery in which a decrease in discharge capacity is suppressed can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic cross-sectional view showing one embodiment of the solid battery disclosed herein.

[0018] Figure 2 Graph showing the relationship between the constraint pressure variation value and the charge amount in Example 1 and Comparative Example 1.

[0019] Figure 3 Graph showing the relationship between the discharge capacity and the number of charge and discharge cycles in Example 1 and Comparative Example 1.

[0020] Figure 4 It is a graph showing the relative resistance values ​​in the solid batteries of Examples 1 to 4 and Comparative Example 1.

[0021] Description of Reference Numerals

[0022] A Negative electrode active material layer

[0023] B Solid electrolyte layer

[0024] C Positive electrode active material layer

[0025] 101 Negative electrode active material

[0026] 102 Solid Electrolyte

[0027] 103 Positive electrode active material

[0028] 105, 107 Conductive additives

[0029] 109, 111 Adhesives

[0030] 113 negative electrode collector

[0031] 115 positive electrode collector DETAILED DESCRIPTION

[0032] The following describes an embodiment as an example of the present disclosure. These descriptions and examples are for illustrative purposes only and do not limit the scope of the present disclosure.

[0033] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as a lower limit and an upper limit.

[0034] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in another stage. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.

[0035] In the present disclosure, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition unless otherwise specified.

[0036] In the present disclosure, a combination of two or more preferred aspects is a more preferred aspect.

[0037] In the present disclosure, the term "layer" includes a case where, when a region where the layer exists is observed, the layer is formed in the entire region and a case where the layer is formed only in a part of the region.

[0038] In the present disclosure, the term "step" includes not only an independent step but also a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step is achieved.

[0039] -Solid-state battery-

[0040] A solid battery according to the present disclosure includes an electrode having: a resin current collector including a resin, a spherical carbon material, and a fibrous carbon material; and an active material layer including an active material.

[0041] According to the present disclosure, a decrease in discharge capacity (for example, capacity retention rate after 150 cycles) can be suppressed. The mechanism of this action is not clear, but it is presumed to be as follows.

[0042] The solid battery disclosed in the present invention has a resin collector. Therefore, compared with the case where the collector is a metal foil, the resin collector easily absorbs the internal stress accompanying the expansion of the electrode, thereby suppressing the pressure applied to the solid battery. Furthermore, in addition to the resin, the resin collector also contains spherical carbon material and fibrous carbon material. Therefore, even in the case where fine cracks caused by volume changes are generated in the active material layer provided on the collector, the spherical carbon material and the fibrous carbon material connect the conductive path, thereby suppressing the reduction of the discharge capacity.

[0043] Hereinafter, “an electrode including a resin current collector including a resin, a spherical carbon material, and a fibrous carbon material; and an active material layer including an active material” is referred to as a “specific electrode”.

[0044] The solid battery disclosed herein includes a so-called all-solid battery using a solid electrolyte as an electrolyte, and the solid electrolyte may also contain less than 10% by mass of an electrolyte relative to the total amount of the electrolyte. Furthermore, the solid electrolyte may be a composite solid electrolyte including an inorganic solid electrolyte and a polymer electrolyte.

[0045] An example of the solid state battery disclosed in the present invention will be described with reference to the drawings. Figure 1 This is a schematic cross-sectional view showing an example of the solid battery of the present disclosure. Figure 1 The solid battery shown includes: a negative electrode including a negative electrode collector 113 and a negative electrode active material layer A, a solid electrolyte layer B, and a positive electrode including a positive electrode collector 115 and a positive electrode active material layer C. The negative electrode active material layer A includes a negative electrode active material 101, a conductive auxiliary agent 105, a binder 109, and a solid electrolyte 102. The positive electrode active material layer C includes a positive electrode active material 103, a conductive auxiliary agent 107, a binder 111, and a solid electrolyte 102. The solid electrolyte layer B may be a single layer or a two-layer structure.

[0046] Figure 1 The solid battery shown only needs to include a specific electrode as at least one of the negative electrode and the positive electrode. When the negative electrode is a specific electrode, the negative electrode collector 113 is a resin collector containing a resin, a spherical carbon material, and a fibrous carbon material. When the positive electrode is a specific electrode, the positive electrode collector 115 is a resin collector containing a resin, a spherical carbon material, and a fibrous carbon material.

[0047] When the combination (set) of the positive electrode, the solid electrolyte layer and the negative electrode is set as a power generation unit, the solid battery may have only one power generation unit or may have two or more power generation units. When the solid battery has two or more power generation units, these power generation units may be connected in series or in parallel.

[0048] In the case where a solid battery has more than two power generation units (i.e., in the case of a stacked battery), it is sufficient that at least one positive electrode or negative electrode is a specific electrode. From the viewpoint of further suppressing the reduction in discharge capacity, the electrode located in the middle of the stacked structure is preferably a specific electrode (for example, the "positive electrode active material layer / collector / positive electrode active material layer" and / or the "negative electrode active material layer / collector / negative electrode active material layer" portion of a stacked battery of "negative electrode active material layer / collector / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / collector / positive electrode active material layer" in the case of a monopolar type, and the "positive electrode active material layer / collector" and / or the "collector / negative electrode active material layer" portion of a stacked battery of "negative electrode active material layer / collector / positive electrode active material layer / solid electrolyte layer / negative electrode active material layer / collector / positive electrode active material layer" in the case of a bipolar type) and the electrodes in all power generation units are preferably specific electrodes.

[0049] The solid battery can seal the stacked end faces (i.e., sides) of the stacked structure of the positive electrode / solid electrolyte layer / negative electrode with a sealing material such as resin. The negative electrode collector 113 and the positive electrode collector 115 can be configured with a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer on the outer peripheral surface.

[0050] The shape of the solid battery is not particularly limited, and may be, for example, a coin shape, a cylinder shape, a square shape, a sheet shape, a button shape, a flat shape, or a stacked shape.

[0051] <Specified Electrode>

[0052] The specific electrode is an electrode including a resin collector containing a resin, a spherical carbon material, and a fibrous carbon material; and an active material layer containing an active material.

[0053] The solid battery involved in the present disclosure only needs to include a specific electrode as at least one of the negative electrode and the positive electrode. The solid battery involved in the present disclosure preferably includes a specific electrode as the negative electrode, and more preferably includes a specific electrode as both the negative electrode and the positive electrode, for example, from the viewpoint of further suppressing the reduction in discharge capacity.

[0054] [Resin current collector]

[0055] The resin current collector contains a resin, a spherical carbon material, and a fibrous carbon material.

[0056] As the resin, for example, known thermoplastic resins such as poly(meth)acrylic acid, poly(methyl)acrylate, polyethylene, polypropylene, polyethylene terephthalate, polyether nitrile, polyimide, polyamide, polytetrafluoroethylene, polyacrylonitrile, poly(meth)acrylate, and vinyl halide resins; thermosetting resins such as epoxy resins, vinyl ester resins, unsaturated polyester resins, phenolic resins, and melamine resins; known conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, polyparaphenylene, polyphenylene vinylene, polyacrylonitrile, and polyoxadiazoles, etc. The resin may be used alone or in combination of two or more.

[0057] Among them, from the viewpoint of further suppressing the peeling of the active material layer from the resin collector and thus reducing the discharge capacity, the resin preferably contains at least one of a thermoplastic resin and a conductive polymer, more preferably contains a thermoplastic resin, and further preferably contains one resin selected from polymethyl (meth)acrylate, polyacrylic acid and polyacrylonitrile.

[0058] In the present disclosure, “(meth)acrylic acid” is a concept including both acrylic acid and methacrylic acid, and “(meth)acrylate” is a concept including both acrylate and methacrylate.

[0059] As for the resin, crystalline resin, amorphous resin and a mixture of the two are all possible. From the viewpoint of improving strength and further inhibiting the active material layer from peeling off from the resin collector and thus reducing the discharge capacity, amorphous resin is preferred. It should be noted that the "crystallinity" of the resin refers to an endothermic peak with a half-peak width of less than 10°C when measured at a heating rate of 10 (°C / min) in differential scanning calorimetry (DSC measurement). On the other hand, the so-called "amorphous" of the resin means that the half-peak width exceeds 10°C or no clear endothermic peak is found.

[0060] The softening temperature of the resin varies depending on the type of resin. For example, from the viewpoint of further suppressing the peeling of the active material layer from the resin collector and thus reducing the discharge capacity, it is preferably 30°C to 100°C, more preferably 30°C to 80°C, and even more preferably 30°C to 75°C.

[0061] The softening temperature of a resin refers to a glass transition temperature determined from a DSC curve obtained by differential scanning calorimetry (DSC).

[0062] The so-called spherical carbon material includes carbon materials whose ratio (hereinafter also referred to as "aspect ratio") of the average length in one direction (such as the short axis) to the average length in another direction (such as the long axis) when the average length is set to 1 is less than 5. That is, in addition to spherical carbon materials, spherical carbon materials also include ellipsoidal carbon materials. As spherical carbon materials, for example, graphites such as natural graphite and artificial graphite; carbon blacks such as acetylene black (AB), Ketjen black (KB), and furnace black; amorphous carbon materials, etc. can be listed. The spherical carbon material can be used alone or in combination of two or more. Among them, from the viewpoint of further suppressing the peeling of the active material layer from the resin collector and thus reducing the discharge capacity, the spherical carbon material preferably contains carbon black, and more preferably contains acetylene black (AB).

[0063] As for the content of the spherical carbon material, from the viewpoint of further suppressing the peeling of the active material layer from the resin collector and thus reducing the discharge capacity, the content is preferably 1 mass % or more and 20 mass % or less, more preferably 1 mass % or more and 15 mass % or less, and further preferably 2 mass % or more and 13 mass % or less, relative to the total solid content of the resin collector.

[0064] As one approach, from the viewpoint of further suppressing the peeling of the active material layer from the resin collector and thus reducing the discharge capacity, the spherical carbon material preferably contains acetylene black (AB), and the content of the spherical carbon material is greater than 2 mass % and less than 13 mass % relative to the total solid content of the resin collector.

[0065] The so-called fibrous carbon material includes fibrous carbon materials having an aspect ratio of 5 or more (more preferably 10 or more). As fibrous carbon materials, for example, carbon nanotubes (CNTs), carbon nanofibers (CNFs), vapor-grown carbon fibers (VGCFs), etc. can be listed. The fibrous carbon material can be used alone or in combination of two or more. Among them, from the viewpoint of further suppressing the peeling of the active material layer from the resin collector and thus reducing the discharge capacity, the fibrous carbon material preferably includes vapor-grown carbon fibers (VGCFs).

[0066] The content of the fibrous carbon material is preferably 10% by mass to 40% by mass, more preferably 12% by mass to 30% by mass, and even more preferably 15% by mass to 25% by mass, relative to the total solid content of the resin collector.

[0067] As one approach, from the viewpoint of further suppressing the peeling of the active material layer from the resin collector and thus reducing the discharge capacity, the fibrous carbon material preferably comprises vapor-grown carbon fiber (VGCF), and the content of the fibrous carbon material is greater than 20 mass % and less than 43 mass % relative to the total solid content of the resin collector.

[0068] The total content of the spherical carbon material and the fibrous carbon material is preferably 10% by mass or more and 50% by mass or less, more preferably 15% by mass or more and 43% by mass or less, and further preferably 15% by mass or more and 35% by mass or less relative to the total solid content of the resin collector. In addition, the content ratio of the spherical carbon material to the fibrous carbon material is preferably 1.0:1.0 to 1.0:10.0, and more preferably 1.0:1.2 to 1.0:8.0.

[0069] From the viewpoint of further suppressing the active material layer from peeling off from the resin current collector and thus reducing the discharge capacity, the resin current collector preferably has a linear expansion coefficient of 100×10 -6 ppm / K or more and 500×10 -6 ppm / K or less, more preferably 200×10 - 6 ppm / K and above 430×10 -6 ppm / K or less, more preferably 230×10 -6 ppm / K and above 350×10 -6 ppm / K or less. The value of the linear expansion coefficient is a value measured by a method in accordance with JIS H7404-1993.

[0070] The method for making the linear expansion coefficient of the resin current collector fall within the above range is not particularly limited, and examples thereof include a method in which the resin in the resin current collector is made to be the above-mentioned preferred resin.

[0071] The thickness of the resin collector is not particularly limited, but is preferably 1 μm to 80 μm, more preferably 1 μm to 50 μm, and even more preferably 1 μm to 30 μm, from the viewpoint of further suppressing a decrease in discharge capacity.

[0072] The thickness of the resin collector is determined by observing a stacked cross section cut in the thickness direction of the resin collector using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX), and measuring the average thickness at 10 arbitrary points.

[0073] There is no particular limitation on the method for forming the resin collector. Examples thereof include: when the resin is thermoplastic, a coating liquid containing the resin and a conductive material is applied, dried and molded; when the resin is thermosetting, raw materials such as a resin precursor or monomer and a conductive material are placed in a mold, heated and cured.

[0074] The resin current collector may further contain other materials other than the resin, the spherical carbon material and the fibrous carbon. Examples of other materials include conductive materials other than the spherical carbon material and the fibrous carbon material, binders, and metal powder materials.

[0075] [Active material layer]

[0076] The active material layer contains an active material. The type of the active material is not particularly limited, and known materials for the negative electrode and the positive electrode can be used.

[0077] The active material may include a Si-based active material.

[0078] Si-based active materials are useful active materials with excellent charge and discharge characteristics. However, the expansion and contraction associated with charge and discharge of Si-based active materials tend to be large, so the active material layer is easily peeled off from the collector, and the discharge capacity is also easily reduced. On the other hand, the solid battery disclosed herein includes a resin collector that contains spherical carbon materials and fibrous carbon materials in addition to the resin. Therefore, compared with the case where the collector is a metal foil, the resin collector easily absorbs the internal stress that accompanies the expansion of the electrode, suppressing the pressure applied to the solid battery. In addition, even in the case where fine cracks caused by volume changes are generated in the active material layer provided on the collector, the spherical carbon material and the fibrous carbon material connect the conductive path, thereby suppressing the reduction in discharge capacity. This is more effective when Si-based active materials are included.

[0079] As the Si-based active material, there is no particular limitation as long as it is a material containing silicon and capable of functioning as an active material, and examples thereof include silicon single substance particles, silicon alloy particles (e.g., alloys of Si and one or more metals selected from Sn, Ti, Fe, Ni, Cu, Co, and Al), porous silicon, silicon inclusion compounds, silicon oxides, and mixtures thereof, etc. The Si-based active material may be used alone or in combination of two or more.

[0080] The active material layer may further contain a solid electrolyte, a binder, and the like in addition to the active material, as necessary.

[0081] There is no particular restriction on the thickness of the active material layer. For example, from the perspective of making the charge and discharge characteristics better and further suppressing the peeling of the active material layer from the resin collector and thus reducing the discharge capacity, the thickness is preferably greater than 0.1 μm and less than 100.0 μm, more preferably greater than 1.0 μm and less than 100.0 μm, and further preferably greater than 30.0 μm and less than 100.0 μm.

[0082] The thickness of the active material layer is determined by observing a cross section of the stack cut in the thickness direction of the active material layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX), and measuring the average thickness at 10 arbitrary points.

[0083] [Middle layer]

[0084] The specific electrode may further include an intermediate layer interposed between the active material layer and the resin current collector, wherein at least one component contained in the active material layer and at least one component contained in the resin current collector are mixed (exist in a mixed state) in the intermediate layer.

[0085] If the specific electrode has an intermediate layer, the peeling of the active material layer from the resin collector is further reduced.

[0086] From the viewpoint of enhancing the anchor effect and further reducing the separation of the active material layer from the resin collector, the intermediate layer is preferably a layer in which at least the active material contained in the active material layer and the resin contained in the resin collector are mixed.

[0087] As for the intermediate layer, from the viewpoint of enhancing the anchoring effect and further reducing the peeling of the active material layer from the resin collector, the thickness of the intermediate layer relative to the thickness of the resin collector (intermediate layer / resin collector) is preferably 1 / 30 or more and 1 / 6 or less, more preferably 1.0 / 30.0 or more and 1.0 / 4.0 or less, further preferably 1.0 / 20.0 or more and 1.0 / 5.0 or less, and even more preferably 1.0 / 10.0 or more and 1.0 / 6.0 or less.

[0088] There is no particular restriction on the thickness of the intermediate layer. For example, from the perspective of making the charge and discharge characteristics better and further inhibiting the active material layer from peeling off from the resin collector and thus reducing the discharge capacity, the thickness is preferably greater than 0.1 μm and less than 15.0 μm, more preferably greater than 0.4 μm and less than 10.0 μm, and further preferably greater than 0.6 μm and less than 8.0 μm.

[0089] The thickness of the intermediate layer is determined by observing a laminate cross section cut in the thickness direction of the intermediate layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX), and measuring the average thickness at 10 arbitrary points.

[0090] The components contained in the intermediate layer can be confirmed by performing EDX analysis on the chemical composition of a laminate cross section cut in the thickness direction of the intermediate layer using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDX).

[0091] There is no particular limitation on the method for forming the intermediate layer, and for example, the following methods can be listed: 1) When the resin in the resin collector is thermoplastic, a method comprising the steps of heating a stack formed by stacking a resin collector comprising a thermoplastic resin (which may further comprise a conductive material) and an active material layer comprising an active material to a temperature above the softening temperature of the thermoplastic resin; and pressing the stack; 2) When the resin in the resin collector is thermosetting, a method of filling a thermosetting resin precursor and the active material, a binder and other components in the active material layer into a mold, and heating the mold to form the stack.

[0092] <Solid electrolyte layer>

[0093] The specific electrode preferably has a solid electrolyte layer. The solid electrolyte layer contains a solid electrolyte. As the solid electrolyte, from the viewpoint of battery performance, it is preferred to contain at least one solid electrolyte selected from a solid electrolyte group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte, and more preferably contains a sulfide solid electrolyte.

[0094] As a sulfide solid electrolyte, it is preferred to contain sulfur (S) as the main component of the anion element, and preferably contain, in addition to S, for example, Li element and A element. The A element is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In. The sulfide solid electrolyte may further contain at least one of O and a halogen element. As the halogen element (X), for example, F, Cl, Br, I, etc. can be listed. There is no particular limitation on the composition of the sulfide solid electrolyte, for example, xLi2S·(100-x)P2S5(70≤x≤80), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.7≤x≤0.8, 0≤y≤30, 0≤z≤30) can be listed. The sulfide solid electrolyte may have a composition represented by the following general formula (1).

[0095] Li 4-x Ge 1-x P x S4(0<x<1)···Formula (1)

[0096] In formula (1), at least a portion of Ge may be replaced by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. In addition, at least a portion of P may be replaced by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. A portion of Li may be replaced by at least one selected from Na, K, Mg, Ca and Zn. A portion of S may be replaced by a halogen. The halogen is at least one selected from F, Cl, Br and I.

[0097] As an oxide solid electrolyte, it is preferred to contain oxygen (O) as the main component of the anion element, for example, it may contain Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W and S.), and O. As oxide solid electrolytes, garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-PO-based solid electrolytes, Li-BO-based solid electrolytes, etc. can be listed. As garnet-type solid electrolytes, for example, Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x ) 12 (0≤x≤2), Li5La3Nb2O 12 Etc. As perovskite-type solid electrolytes, for example, (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. can be cited. As NASICON-type solid electrolytes, for example, Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. can be cited. As Li-PO-based solid electrolytes, Li3PO4 and LIPON (compounds in which a part of O in Li3PO4 is replaced by N) can be cited. As Li-BO-based solid electrolytes, Li3BO3 and compounds in which a part of O in Li3BO3 is replaced by C can be cited.

[0098] As the halide solid electrolyte, a solid electrolyte containing Li, M and X is preferred (M represents at least one of Ti, Al and Y, and X represents F, Cl or Br). Specifically, Li 6-3z Y z X6 (X represents Cl or Br, and z represents 0<z<2.), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5). 6-3z Y z Among X6, Li3YX6 (X represents Cl or Br) is more preferred from the viewpoint of excellent lithium ion conductivity, and Li3YCl6 is further preferred. In addition, for example, from the viewpoint of suppressing oxidative decomposition of sulfide solid electrolytes, it is preferred to contain Li3YX6 together with solid electrolytes such as sulfide solid electrolytes. 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5).

[0099] <Application>

[0100] As the purpose of the solid battery disclosed in the present invention, a typical solid secondary battery (more preferably a solid lithium ion secondary battery) can be used. For solid batteries, power sources such as vehicles, electronic devices, and electrical storage can be listed. As vehicles, electric four-wheeled vehicles, electric two-wheeled vehicles, gasoline vehicles, diesel vehicles, etc. can be listed. As electric four-wheeled vehicles, for example, electric vehicles (BEV), plug-in hybrid electric vehicles (PHEV), and hybrid electric vehicles (HEV) can be listed. Among them, the purpose of the solid battery disclosed in the present invention is preferably a driving power supply for hybrid electric vehicles, plug-in hybrid electric vehicles or electric vehicles.

[0101] Example

[0102] <Example 1>

[0103] [Production of positive electrode]

[0104] The NCA-based positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 The positive electrode composite material of NCA-based positive electrode active material: sulfide-based solid electrolyte: vapor-grown carbon fiber: PVdF-based binder in the positive electrode slurry was stirred with an ultrasonic dispersion device to prepare a positive electrode slurry. The mass ratio of NCA-based positive electrode active material: sulfide-based solid electrolyte: vapor-grown carbon fiber: PVdF-based binder in the positive electrode slurry was adjusted to 88.2:9.8:1.3:0.7. The positive electrode slurry was applied to Al foil and SUS foil respectively by a doctor blade method, and these were dried on a hot plate at 100°C for 30 minutes to obtain two positive electrodes with positive electrode active material layers.

[0105] [Production of negative electrode]

[0106] The negative electrode composite material including powdered Si particles (Si-based negative electrode active material) as raw materials, sulfide-based solid electrolyte (Li2S-P2S5), conductive material (VGCF), PVdF-based binder and butyl butyrate was stirred using an ultrasonic dispersion device to prepare a negative electrode slurry. The mass ratio of powdered Si particles: sulfide-based solid electrolyte: carbon material: PVDF-based binder in the negative electrode slurry was adjusted to 100:77.6:2:15. The negative electrode slurry was applied to Ni foil and SUS foil respectively using a doctor blade method, and these were dried on a hot plate at 100°C for 30 minutes to obtain two negative electrodes with negative electrode active material layers.

[0107] [Fabrication of Solid Electrolyte Layer]

[0108] A solid electrolyte composite material containing a sulfide-based solid electrolyte (Li2S-P2S5) as a raw material, a PVDF-based binder and butyl butyrate was stirred using an ultrasonic dispersion device to prepare a solid electrolyte slurry. The solid electrolyte slurry was adjusted in such a way that the mass ratio of the sulfide-based solid electrolyte: PVDF-based binder was 99.4:0.4. The solid electrolyte slurry was applied to each positive electrode active material layer of the two positive electrodes prepared above using a doctor blade method, and a stack of solid electrolyte layer / positive electrode active material layer / Al foil (solid electrolyte layer / positive electrode) and a stack of solid electrolyte layer / positive electrode active material layer / SUS foil (solid electrolyte layer / positive electrode) were obtained, respectively.

[0109] [Production of Resin Current Collector]

[0110] The conductive paste obtained by mixing the spherical carbon material (AB, aspect ratio 1-5) of the type and amount shown in Table 1, the fibrous carbon material (VGCF, aspect ratio 10-500) of the type and amount shown in Table 1, polymethyl methacrylate (amorphous resin) and butyl butyrate as resins was applied on a PET film by a doctor blade method, and after drying at 150° C. for 30 minutes, the PET film was peeled off to obtain a resin current collector. In addition, the glass transition temperature (i.e., softening temperature) of the resin is less than the crystallization temperature of the solid electrolyte.

[0111] [Production of Laminated Body]

[0112] The two types of positive electrode / solid electrolyte layers prepared above and the two types of negative electrodes were stacked in the following combinations to obtain two pseudo-stacks.

[0113] ·Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / SUS foil

[0114] ·SUS foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil

[0115] Next, the two quasi-laminates are respectively pressed by a roller press at a pressing pressure of 50 kN / cm and a temperature of 160°C. Then, the SUS foils are peeled off from the quasi-laminates, and a resin collector is arranged between the laminates from which the SUS foils are peeled off, and the laminates are stacked to obtain a laminate having a laminate structure of "Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / resin collector / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil". Then, the laminate is pressed by a roller press at a pressing pressure of 20 kN / cm and a temperature of 160°C. Next, cut into 1 cm 2size, thereby obtaining a solid battery with a stacked structure of "Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / intermediate layer / resin collector / intermediate layer / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil".

[0116] <Example 2 to Example 4>

[0117] A resin collector was obtained in the same specifications as in Example 1 except that the amounts of the spherical carbon material and the fibrous carbon material were set as shown in Table 1. A solid battery was obtained in the same specifications as in Example 1 except that the obtained resin collector was used.

[0118] <Comparative Example 1>

[0119] [Production of positive electrode]

[0120] The NCA-based positive electrode active material (LiNi 0.8 Co 0.15 Al 0.05 The positive electrode composite material of NCA-based positive electrode active material: sulfide-based solid electrolyte: vapor-grown carbon fiber: PVdF-based binder in the positive electrode slurry was adjusted to 88.2:9.8:1.3:0.7. The positive electrode slurry was coated on Al foil by a doctor blade method and dried on a hot plate at 100°C for 30 minutes to obtain a positive electrode with a positive electrode active material layer.

[0121] [Production of negative electrode]

[0122] The negative electrode composite material including powdered Si particles as raw materials, sulfide-based solid electrolyte (Li2S-P2S5), conductive material (VGCF), PVDF-based binder and butyl butyrate was stirred using an ultrasonic dispersion device to prepare a negative electrode slurry. The mass ratio of powdered Si particles: sulfide-based solid electrolyte: carbon material: PVDF-based binder in the negative electrode slurry was adjusted to 100:77.6:2:15. The negative electrode slurry was applied to Ni foil using a doctor blade method and dried on a hot plate at 100°C for 30 minutes to obtain a negative electrode with a negative electrode active material layer.

[0123] [Fabrication of Solid Electrolyte Layer]

[0124] A solid electrolyte composite material containing a sulfide-based solid electrolyte (Li2S-P2S5) as a raw material, a PVDF-based binder, and butyl butyrate was stirred using an ultrasonic dispersion device to prepare a solid electrolyte slurry. The solid electrolyte slurry was adjusted in such a way that the mass ratio of the sulfide-based solid electrolyte: PVDF-based binder was 99.4:0.4. The solid electrolyte slurry was applied to the positive electrode active material layer of the positive electrode prepared above using a doctor blade method to obtain a laminate of solid electrolyte layer / positive electrode active material layer / Al foil (solid electrolyte layer / positive electrode).

[0125] [Production of Laminated Body]

[0126] The positive electrode / solid electrolyte layer and the negative electrode prepared above were stacked in the following combination to obtain a stacked body.

[0127] Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil

[0128] Next, the laminate was pressed with a roll press at a pressing pressure of 50 kN / cm and a temperature of 160° C. Next, the laminate was punched out into 1 cm 2 size, thereby obtaining a solid battery having a stacked structure of “Ni foil / negative electrode active material layer / solid electrolyte layer / positive electrode active material layer / Al foil”.

[0129] <Evaluation of charging limit pressure>

[0130] The solid batteries of Example 1 and Comparative Example 1 were clamped between two restraining plates, and the two restraining plates were fastened with a fastener at a restraining pressure of 5 MPa to fix the distance between the two restraining plates. Next, the restrained stack was charged at a constant current of 1 / 10C until 8.10V, and then charged at a constant voltage of 8.10V until the termination current was 1 / 100C. Then, the restraining pressure before and after charging was recorded. The restraining pressure P before charging was recorded. 之前 The constraint pressure P at the end of charging 之后 The difference (P 之前 -P 之后 The value obtained by dividing the absolute value of ) by the discharge capacity is defined as the constraint pressure variation value. The larger the constraint pressure variation value, the greater the expansion of the solid battery associated with charging.

[0131] Figure 2 Graph showing the relationship between the constraint pressure variation value and the charge amount in Example 1 and Comparative Example 1. Figure 2 As shown, the solid battery of Example 1 suppresses the fluctuation of the confinement pressure accompanying charging as compared with the solid battery of Comparative Example 1.

[0132] <Evaluation of discharge capacity>

[0133] Using a galvanometer, 50 cycles of charge and discharge tests were performed under the conditions of a current of 0.1C, a charge termination voltage of 8.10V, and a discharge termination voltage of 5.0V. Starting from charging, after completing one charge, the current required for discharge to 5.0V was calculated and divided by the weight of the active material used in the measurement to calculate the discharge capacity in each cycle. Then, the 150th discharge capacity was divided by the first discharge capacity to obtain the capacity retention rate (%) after 150 cycles. The results are shown in Table 1.

[0134] Figure 3 Graph showing the relationship between the discharge capacity and the number of charge and discharge cycles in Example 1 and Comparative Example 1. Figure 3 As shown, it can be seen that the solid battery of Example 1 is superior to the solid battery of Comparative Example 1 in capacity retention rate, that is, the decrease in discharge capacity is suppressed.

[0135] <Evaluation of resistance value>

[0136] The solid batteries of Examples 1 to 4 and Comparative Example 1 were clamped between two restraining plates, and the two restraining plates were fastened with a fastener at a restraining pressure of 5 MPa to fix the distance between the two restraining plates. Next, the constrained stack was charged at a constant current of 1 / 10C to 8.10V, and then, charged at a constant voltage of 8.10V to a termination current of 1 / 100C. Furthermore, a constant current discharge of 1 / 10C to 5.0V was performed, and then, a constant voltage discharge of 5.0V to a termination current of 1 / 100C was performed. Then, the absolute value of the difference between the voltage before charging and the voltage after 0.1 second discharge was divided by the current equivalent to 1 / 100C to calculate the resistance value. The obtained resistance value is shown as a relative value relative to the resistance value in the solid battery of Comparative Example 1. Figure 4 .

[0137] Figure 4 Graph showing relative resistance values ​​in solid batteries of Examples 1 to 4 and Comparative Example 1. Figure 4 As shown, it can be seen that the solid battery of Example has suppressed the increase in resistance value due to the separation of the active material layer from the current collector, as compared with the solid battery of Comparative Example 1.

[0138]

[0139] As shown in Table 1, it can be seen that the solid battery of the example is superior in capacity retention rate, that is, the decrease in discharge capacity is suppressed, as compared with the solid battery of the comparative example.

Claims

1. A solid battery comprising an electrode, wherein the electrode comprises: a resin current collector comprising a resin, a spherical carbon material, and a fibrous carbon material; and An active material layer comprising an active material.

2. The solid battery according to claim 1, wherein: The active material includes a Si-based active material.

3. The solid battery according to claim 1 or 2, wherein: The resin has a softening temperature of 30° C. or higher and 80° C. or lower.

4. The solid battery according to claim 1 or 2, wherein: The spherical carbon material includes acetylene black (AB), and the content of the spherical carbon material is 2 mass % or more and 13 mass % or less relative to the total solid content of the resin current collector.

5. The solid battery according to claim 1 or 2, wherein: The fibrous carbon material includes vapor grown carbon fiber (VGCF), and the content of the fibrous carbon material is 15 mass % or more and 25 mass % or less relative to the total solid content of the resin current collector.

Citation Information

Patent Citations

  • Battery system

    JP2017112029A